2002
DOI: 10.1017/s1047951102000252
|View full text |Cite
|
Sign up to set email alerts
|

“Masked” pulmonary venous obstruction in patients with isomerism of the right atrial appendages: an overstated association

Abstract: Isomerism of the right atrial appendages is associated with anomalies of pulmonary venous return, which may be obstructive. The associated pulmonary arterial obstruction, however, has been reported to "mask" the pulmonary venous obstruction, with resultant pulmonary edema following augmentation of the flow of blood to the lungs. We postulated that the frequency of "masked" pulmonary venous obstruction has been over-reported in the literature. To ascertain the true situation, we evaluated the frequency of "mask… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(54 citation statements)
references
References 13 publications
0
54
0
Order By: Relevance
“…Optimal management of the two sub-sets remains nebulous. [14][15][16][17][18][19][20][21][22][23][24][25]38 The subsets, nonetheless, are best segregated on the basis of right versus left isomerism. The markedly different features will post different surgical challenges.…”
Section: Surgical Managementmentioning
confidence: 99%
See 3 more Smart Citations
“…Optimal management of the two sub-sets remains nebulous. [14][15][16][17][18][19][20][21][22][23][24][25]38 The subsets, nonetheless, are best segregated on the basis of right versus left isomerism. The markedly different features will post different surgical challenges.…”
Section: Surgical Managementmentioning
confidence: 99%
“…Moderately hypothermic cardiopulmonary bypass at 32°C, using cold blood cardioplegia, is now the most popular technique, replacing continuous cardiopulmonary bypass with low-flow perfusion, brief periods of deep hypothermic circulatory arrest, and deep hypothermic circulatory arrest with selective cerebral perfusion. [14][15][16][17][18][19][20][21][22][23][24][25]38 Venous cannulation can be problematic in both subsets because of the systemic venous anomalies. Direct cannulation is preferred because of the likely complexity of any intraatrial repair.…”
Section: Surgical Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…More recent data now suggests that such masked pulmonary venous obstruction may be less common than once thought. 142 Failure to define the arrangement of the pulmonary veins preoperatively, nonetheless, results in high surgical mortality, with the findings reported in 2000 by Chowdhury et al 143 providing validation for the concern expressed much earlier by DeLeon et al 144 These observations are further supported by the experience reported by Jenkins et al, 145 showing that, in the setting of totally anomalous pulmonary venous connection, a small sum of the diameters of the individual pulmonary veins, a small confluence, and the presence of heterotaxy syndrome were all significant predictors of survival in univariate analysis. Multivariate analysis showed that the small size of the pulmonary veins was a strong adverse predictor of survival independent of the presence of heterotaxy.…”
Section: Outcomes For Patients With Right Isomerismmentioning
confidence: 99%